GAMBARAN FISIK DAN PSIKOLOGIS PENDERITA KANKER PAYUDARA POST MASTEKTOMI DI RSUP SANGLAH DENPASAR TAHUN 2014 - Sri Guntari, Gusti Agung; Suariyani, Ni Luh Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 3 No 1 (2016): Juni (2016), 2016)
Cancer is a non-communicable disease and remains a public health problem in the world. The type of cancer commonly found in women is breast cancer. Advancements in medical technology have led to new treatments for breast cancer, one of them is the mastectomy. This treatment can affect the physical and/or psychological aspect of the patient. The purpose of this study was to know patients condition with breast cancer at the Sanglah Hospital Denpasar from physical and psychological aspects post-mastectomy. This research was a cross-sectional descriptive study. This study involved 41 respondent with breast cancer post- mastectomy with consecutive sampling. Results showed that 34.1% of respondents were below 40 years old and 51.2% had low education level. In physical aspects, the result showed that most breast cancer post -mastectomy patients had a good physical condition (48.8%) and about 53.7% were unproductive. In psychological aspects, 56.1% patients had minimal depression level, and 90.2% patients had positive body image . Among patients with the bad physical condition, 91.7% were unproductive. Meanwhile, 50% of patients with depression were unproductive and 50% of patients with negative body image were also unproductive. Most of the patients were still unable to do formal work. Therefore, it is advised that patients participate in light physical activities to increase productivity with the possibility of producing something with economic value. Those efforts are part of tertiary prevention, especially rehabilitation process.
Keywords: mastectomy, the physical condition, the level of depression, body image, productivity, Sanglah Hospital